An Analysis of the Use of Verbal and Nonverbal Messages in WhatsApp Group Chats Done By Nk Students of English Department of Universitas Negeri Padang - Ramel Nadia Chesca; Jufri Jufri; Saunir Saun (English Language and Literature, 2019)
Language is the oldest tool of communication which already exists from the first time humans were created. The use of language, at first and with the simplest form, is the form of nonverbal, which is language of symbol, sign, body language, face expression, and gesture forms. However, the study of language as a field of linguistics is the language in the form of words, or can be called as academic language. But, even academic language also has errors in their written conversation. Even less, these errors are done by the academic people itself. Based on the analysis of the data, it can be seen that there are 6 types of conversations occur in WhatsApp Group Chats “SASING UNP” and has 24% of error from total data that analysed was 118 utterances. However, another result of this research proved the hypothesis of researcher, which the dominant conversation happened, was used both verbal and nonverbal.